Management of mucopolysaccharidosis type IH (Hurler's syndrome) presenting in infancy with severe dilated cardiomyopathy: a single institution's experience. Issue 2 (21st June 2012) - Wiseman, Daniel H.; Mercer, Jean; Tylee, Karen; Malaiya, Nilima; Bonney, Denise K.; Jones, Simon A.; Wraith, J Edmond; Wynn, Robert F.
Abstract: Mucopolysaccharidosis type IH (MPSIH) is a lysosomal storage disorder whose untreated course involves progressive multisystem deterioration and death within the first decade of life. Allogeneic haematopoietic stem cell transplantation (HSCT) is an established treatment modality that improves functional outcome and long‐term survival. Optimal outcome requires transplantation early in life and with myeloablative conditioning. Severe cardiomyopathy can be present at diagnosis and may seemingly preclude this approach. We performed a retrospective review of those cases transplanted in Manchester since 2000 that initially presented with established cardiomyopathy, with a view to identifying general management principles. Of 44 MPSIH children transplanted in this period, 6 had displayed moderate or severe cardiomyopathy at presentation; symptomatic cardiac failure was the predominant presenting feature in five of these. Echocardiographic and clinical improvement in cardiac function was observed with extended enzyme replacement therapy (ERT) in all cases, with recovery of fractional shortening to ≥25 % achieved in all patients before coming to transplant (after median 19 weeks ERT). All were transplanted successfully, with good functional and cardiologic outcomes. However, cyclophosphamide conditioning was implicated in acute post‐transplant cardiac decompensation in several cases. Our experiences highlight three important messages: (1) A diagnosis of MPSIH should be considered in any infant presenting with unexplained severe cardiac failure; (2) ERT pre‐transplant can improve cardiac function sufficiently to permit safe HSCT using myeloablative conditioning; and (3) High dose cyclophosphamide should be avoided in conditioning these patients.